1983
DOI: 10.1017/s0043174500068983
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CGA-43089 on Responses of Sorghum (Sorghum Bicolor) to Metolachlor Combined by Ozone or Antioxidants

Abstract: In greenhouse studies, the potential interactive effects of metolachlor [2-chloro-N-(2-ethyl-6-methylphenyl)-N-(2-methoxy-1-methylethyl)acetamide] treatments combined with the air pollutant ozone (O3) or the antioxidants, piperonyl butoxide {α-[2-butoxyethyl) ethoxy]-4,5-dimethylenedioxy-2-propyltoluene} andn-propyl gallate, on the growth of sorghum [Sorghum bicolor(L.) Moench ‘Funk G522DR’] seedlings that were protected or unprotected with the antidote, CGA-43089 [α-(cyanomethoximino)-benzacetonitrile], were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 16 publications
1
10
0
1
Order By: Relevance
“…However, our greenhouse results show that atrazine at 1.12 kg/ha reduced growth of grain sorghum in the absence of any visible damage. Although studies showed that cyometrinil can protect grain sorghum against damage by metolachlor and alachlor (11,29), some reports indicated these herbi cides reduced grain sorghum growth even in the presence of this safener (15,17). Our results agree with those of the latter and show that metolachlor and alachlor caused re ductions in all growth parameters that were determined at plant maturity (Table 2).…”
Section: • Control • Atrazi Ne E3 M E T O L a C H L O R E3 Atr + M E supporting
confidence: 90%
“…However, our greenhouse results show that atrazine at 1.12 kg/ha reduced growth of grain sorghum in the absence of any visible damage. Although studies showed that cyometrinil can protect grain sorghum against damage by metolachlor and alachlor (11,29), some reports indicated these herbi cides reduced grain sorghum growth even in the presence of this safener (15,17). Our results agree with those of the latter and show that metolachlor and alachlor caused re ductions in all growth parameters that were determined at plant maturity (Table 2).…”
Section: • Control • Atrazi Ne E3 M E T O L a C H L O R E3 Atr + M E supporting
confidence: 90%
“…Whereas earlier experimental results and ideas did not support related modes of action for the different safeners known, more recent data has opened the possibility for a unifying concept (Fedtke, 1985). This concept begins with the observation of synergistic interactions between the insecticide synergist and mono-oxygenase inhibitor PBO and the herbicides metolachlor (Hatzios, 1983c) and EPTC (Hatzios, 1983b), both with and without safeners. Conversely, several herbicide safeners, and also the herbicide metolachlor, can act as insecticide synergists (Ketchersid, Plapp & Merkle, 1985), suggesting that these safeners and herbicides can act as mono-oxygenase inhibitors in insects.…”
Section: Safener Relationshipsmentioning
confidence: 99%
“…Exposure conditions in the growth chamber were 24 ± 2 C, 65 ± 3% relative humidity, and 400 pE-nr 2 s" 2 photosynthetic photon flux density provided by mixed incandescent and fluorescent lighting. Exposure to 0 3 was initiated after plants were preequilibrated in the chamber for 2 h. Untreated seedlings were placed in another growth chamber with similar conditions for 6 h. 0 3 was generated by passing dry air through an ozone generator 3 . O3 concentrations in the growth chamber at plant height were monitored with a Monitor Labs Model 8410 O3 analyzer 4 .…”
Section: Methodsmentioning
confidence: 99%
“…Ozone may interact with herbicides on certain crop plants, thereby modifying either the plant response to herbicides (1, 2,3,4,14) or the metabolism of herbi cides in fumigated plants (7,8,9,10). For example, pebulate (5-propyl butylethylcarbamothioate) and chloramben (3-amino-2,5-dichlorobenzoic acid) can in teract synergistically with O3 on selected cultivars of tobacco (Nicotiana tabacum L.) (1).…”
Section: Introductionmentioning
confidence: 99%